Associations of self-reported sleep quality and duration with dietary eating behaviours: a cross-sectional study of 27,263 UK adults - Scott A. Willis; Arwa Alruwaili; Iuliana Hartescu; Kevin Deighton; Christopher Goodwin; Joseph Henson; Alice E. Thackray; David J. Stensel; James A. King (Appetite, 2026)

Changing climate and disturbance effects on southwestern US forests - Matthew D. Hurteau; Reese Baker; Kyle Gonterman; Abigail Granath; Josh Lopez-Binder; M. Dylan Taylor; Lorraina S. Rojas; Lindsey Rotche; Andy Graves; Marissa J. Goodwin; Gavin Jones; Christopher Marsh (Forest Ecology and Management, 2025)

Lake Erie field trials to advance autonomous monitoring of cyanobacterial harmful algal blooms - Paul A. Den Uyl; Luke R. Thompson; Reagan M. Errera; James M. Birch; Christina M. Preston; William Ussler; Colleen E. Yancey; Subba Rao Chaganti; Steven A. Ruberg; Gregory J. Doucette; Gregory J. Dick; Christopher A. Scholin; et al. (Frontiers in Marine Science, 2022)
Biomolecular analyses are used to investigate the dynamics of cyanobacterial harmful algal blooms (cyanoHABs), with samples collected during monitoring often analyzed by qPCR and sometimes amplicon and metagenomic sequencing. However, cyanoHAB research and monitoring programs face operational constraints due to the reliance on human resources for sample collections. To address this impediment, a third-generation Environmental Sample Processor (3G ESP) integrated with a long-range autonomous underwater vehicle (LRAUV) was tested during seasonal blooms of Microcystis in western Lake Erie (WLE) in 2018 and 2019. The LRAUV-3G ESP successfully performed flexible, autonomous sampling across a wide range of cyanoHAB conditions, and results indicated equivalency between autonomous and manual methods. No significant differences were found between LRAUV-3G ESP and manual sample collection and handling methods in the 12 parameters tested. Analyzed parameters included concentrations of total cyanobacteria and microcystin toxin gene via qPCR; relative abundances of bacterial amplicon sequence variants (ASVs) from 16S rRNA gene amplicon sequencing; and community diversity measures from both 16S amplicon and metagenomic sequencing. The LRAUV-3G ESP provided additional sampling capacity and revealed differences between field seasons for bacterial taxa and concentrations of total cyanobacteria and microcystin toxin gene. Metagenomic analysis of multiple microcystin toxin genes corroborated the use of the mcyE gene as a proxy for the genomic potential of WLE cyanoHABs to produce microcystin. Overall, this study provides support for the use of autonomous ‘omics capability in WLE to help expand the spatial and temporal coverage of cyanoHAB monitoring operations.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Observing Life in the Sea Using Environmental DNA - Francisco Chavez; Markus Min; Kathleen Pitz; Nathan Truelove; Jacoby Baker; Diana LaScala-Grunewald; Marguerite Blum; Kristine Walz; Charles Nye; Anni Djurhuus; Robert Miller; Kelly Goodwin; et al. (Oceanography, 2021)
The use of environmental DNA (eDNA) for studying the ecology and variability of life in the sea is reviewed here in the context of US interagency Marine Biodiversity Observation Network (MBON) projects. Much of the information in this paper comes from samples collected within US National Marine Sanctuaries. The field of eDNA is relatively new but growing rapidly, and it has the potential to disrupt current paradigms developed on the basis of existing measurement methods. After a general review of the field, we provide specific examples of the type of information that eDNA provides regarding the changing distribution of life in the sea over space (horizontally and vertically) and time. We conclude that eDNA analyses yield results that are similar to those collected using traditional observation methods, are complementary to them, and because of the breadth of information provided, have the potential to improve conservation and management practices. Moreover, through technology development and standardization of methods, eDNA offers a means to scale biological observations globally to a level similar to those currently made for ocean physics and biogeochemistry. This scaling can ultimately result in a far better understanding of global marine biodiversity and contribute to better management and sustainable use of the world ocean. Improved information management systems that track methods and associated metadata, together with international coordination, will be needed to realize a global eDNA observation network.

In situ Autonomous Acquisition and Preservation of Marine Environmental DNA Using an Autonomous Underwater Vehicle - Kevan M. Yamahara; Christina M. Preston; James Birch; Kristine Walz; Roman Marin; Scott Jensen; Douglas Pargett; Brent Roman; William Ussler; Yanwu Zhang; John Ryan; Brett Hobson; et al. (Frontiers in Marine Science, 2019)

Aerobic and anaerobic de-epoxydation of mycotoxin deoxynivalenol by bacteria originating from agricultural soil - Rafiqul Islam; Ting Zhou; J. Christopher Young; Paul H. Goodwin; K. Peter Pauls (World Journal of Microbiology and Biotechnology, 2012)

Minimizing Variability of Cascade Impaction Measurements in Inhalers and Nebulizers - Matthew Bonam; David Christopher; David Cipolla; Brent Donovan; David Goodwin; Susan Holmes; Svetlana Lyapustina; Jolyon Mitchell; Steve Nichols; Gunilla Pettersson; Chris Quale; Nagaraja Rao; et al. (AAPS PharmSciTech, 2008)